Internal Kualitas internal dan eksternal telur ayam lokal yang di inseminasi buatan menggunakan mikropipet - Agus restu budimas; Ristika Handarini; Agung Puji Haryanto (Fakultas Pertanian Universitas Majalengka, 2023)
Native chicken is a species of fowl that is usually consumed by people in Indonesia. Most various of native chicken bred are new strains, i.e Merawang chicken, Kampung Unggul Balitbang (KUB) chicken and IPB D-1 chicken. High-quality chicken shall be produced from superior breed through artificial insemination by micropipette. A micropipette is a pipette tool with high accuracy and precision to collect cement when performing an artificial insemination. This research is performed to test the internal and external quality of egg which involves egg yolk index (IKT), haugh unit (HU), eggshell weight and egg weight of 3 types of native chickens that artificially inseminated by a micropipette of various doses using 108 female native chickens aged 50 weeks and 6 males native chickens aged 24 months. The treatment was applied to the object with details of 36 female KUB and 2 males KUB, 36 females Merawang and 2 males Merawang, and 36 females IPB D-1 and 2 males IPB-D1. The quality test of eggs used 72 eggs which consists of total each type of chicken are 24 eggs. Data were analyzed using Completely Randomized Design (CRD). Factors that affect internal and external quality are age, genetics, health, environment, storage time, and feed. Research could be followed to conduct hatchability tests on the eggs produced from this study to trace an effect on egg hatchability in various types of native chickens.